Susceptibility Pattern, Genotyping, and Mutations of Klebsiella pneumoniae at Dr. H. Abdul Moeloek General Hospital - Hidayat Hidayat; Ida Parwati; Eko Agus Srianto (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2024)
Klebsiella pneumoniae is one of the most common causes of severe hospital-acquired infection. ESBL-producing Klebsiella pneumoniae causes a major problem for clinical management and epidemiological study. The other factor identified was OmpK35 which is often poorly or not expressed and it can be altered by factors such as point mutations. This study aimed to determine the susceptibility pattern, and the genotyping and to investigate the mutations in OmpK35 of Klebsiella.pneumoniae. This is a cross-sectional study using susceptibility pattern data from the ninety isolates of Klebsiella pneumoniae from the patients admitted to Dr. H. Abdul Moeloek General Hospital, Lampung. The Genotype of ESBL genes and OmpK35 gene were determined by polymerase chain reaction and sequencing for identification of the mutation. The susceptibility rate of Klebsiella pneumoniae belonged to Ampicillin was 0%. The susceptibility rate belonged to Amikacin (96.6%), Meropenem (94.4%), and Ertapenem (94.4%).  From 90 isolates, the genotype blaSHV was found in 86.7%, and most of the isolates had OmpK35 genes (91.2%). Among the thirty isolates, 20% harbored mutations in the OmpK35 protein with substitution mutations. This finding indicated a high prevalence of antibiotic resistance, a high prevalence rate of ESBL gene production, and a high frequency of porin mutations among Klebsiella pneumoniae isolates.